2013
DOI: 10.1371/journal.pone.0082850
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Subacute Ruminal Acidosis (SARA) on Milk Quality and Hepatic Gene Expression in Lactating Goats Fed a High-Concentrate Diet

Abstract: PurposeThe mechanism underlying the decline in milk quality during periods of feeding high-concentrate diets to dairy ruminants is not well documented. The aim of this study was to investigate the metabolic changes in the liver that contribute to the input of substrate precursors to the mammary gland after feeding a high-concentrate diet to lactating goats for a long period.Experimental DesignEight mid-lactating goats with rumen cannulas were randomly assigned to two groups. For 9 weeks, the treatment group wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
83
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 54 publications
12
83
3
2
Order By: Relevance
“…Significantly lower ruminal pH was observed in HC goats compared with LC goats, which was accompanied with greater VFA concentrations in ruminal fluids. These results were consistent with our previous studies (Dong et al, 2013;Jia et al, 2014;Tao et al, 2014;Tao et al, 2015). In those studies SARA were experimentally induced by feeding 65% concentrate diet for 2 months.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Significantly lower ruminal pH was observed in HC goats compared with LC goats, which was accompanied with greater VFA concentrations in ruminal fluids. These results were consistent with our previous studies (Dong et al, 2013;Jia et al, 2014;Tao et al, 2014;Tao et al, 2015). In those studies SARA were experimentally induced by feeding 65% concentrate diet for 2 months.…”
Section: Discussionsupporting
confidence: 93%
“…As a consequence, the ruminant microbial ecology and systemic metabolic state will change because of the rapid fermentation and subsequent excessive organic acids accumulation, and such animals are likely to suffer metabolic disorders such as acidosis, fatty liver, laminitis and even systemic inflammation (Alegre et al, 1988;Kleen et al, 2003;Plaizier et al, 2008;Dong et al, 2011;Tao et al, 2014). Our previous studies also showed that long-term feeding of a 65% high concentrate (HC) diet to lactating dairy goats led to subacute ruminal acidosis (SARA) and disruptions of mucosal barrier in the hindgut (Dong et al, 2013;Tao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown previously that the LPS concentrations in both ruminal contents and blood increased after 21% dry matter in the control diet with a concentrate to roughage ratio of 50∶50 was replaced with a grain mixture comprised of 50% ground wheat and 50% ground barley [15]. The presence of LPS in the blood of dairy cows and goats fed diets containing a high proportion of concentrate was also reported in several studies [29] [30] [31]. Therefore, the lower histone H3 acetylation in the mammary tissue of cows fed the HCS diet can be attributed to the increased entry of LPS into the mammary tissue.…”
Section: Discussionsupporting
confidence: 65%
“…These findings were in agreement with Dong et al, (2013); also these results were confirmed by Bipin et al (2016).…”
Section: Discussionsupporting
confidence: 91%